Theatrical Characteristics Behind Immersivity Through the Idea of “Arche-Screen”: : A First Case Study - Melchiorri, Francesco (Mimesis Journal, 2024)
Festen. Il gioco della verità (2021) by Il Mulino di Amleto is the first Italian drama adaptation of the early Dogma 95 movie Festen by Thomas Vinterberg. The original staging puts in dialogue different media in a constant, simultaneous double storyline representation: using a live camera they shoot a part of the pièce constantly, in a non-stop sequence on stage, screened on a transparent canvas which frame the entire proscenium. Festen would be considered a case study to question interesting issues around the idea of immersivity intersecting with Mauro Carbone’s idea of «arche-screen», to suggest an innovative standpoint on heritage.